METHOD DEVELOPMENT FOR METAL ANALYSIS USING BOUGAINVILLEA FLOWER EXTRACTS AND ULTRAVIOLET-VISIBLE SPECTROSCOPY TECHNIQUE - Hongkrengkai, Rattapon; Tratip, Jutamanee; Rittisak, Supawinee; Kumtabtim, Usarat (Srinakharinwirot University Journal of Sciences and Technology, 2024)
This research aims to develop a method for metal analysis with Bougainvillea flower or paper flower extracts and Ultra-Visible spectroscopy techniques. The paper flower extracts that used in this study were extracted with buffer solution. The chemical structure of paper flower extracts was determined by Fourier transform infrared spectroscopy (FT-IR) technique. The result showed that the functional groups of paper flower extracts were similar to betanin standard that produced from beetroot. The optimum condition for metal analysis with developed method included the buffer solution (pH 7) that used as extraction solvent, the concentration of betanin in paper flower extracts of 2.8 grams per liter. The reaction time was 10 minutes. The linearity range of nickel standard solution was 2.5-40 milligrams per Liter. This method was detected at the wavelength of 536 nanometer. The limit of detection was 2.92 milligrams per liter. The linear equation was y = -0.0045x+0.6096. The coefficient of determination (R2) was 0.9857. The relative standard deviation of reproducibility and repeatability were 0.65 and 0.18 percentage, respectively. The recovery was 91-96 percentage. The result of nickel content in synthetic wastewater from developed method showed correlated with Flam-AAS technique. This developed method is simple, rapid, cheap and environmentally friendly.